Radiographic Impact of Lapidus, Proximal Lateral Closing Wedge Osteotomy, and Suture Button Procedures on First Ray Length and Dorsiflexion for Hallux Valgus. (August 2020) - Foran, Ian M.; Mehraban, Nasima; Jacobsen, Stephen K.; Bohl, Daniel D.; Lin, Johnny; Lee, Simon; Holmes, George B.; Hamid, Kamran S.
Background: Shortening and dorsiflexion of the first metatarsal are known potential side effects of metatarsal osteotomies for hallux valgus (HV) with the potential to cause transfer metatarsalgia. We compared the effect of the first tarsometatarsal joint arthrodesis (Lapidus procedure), proximal lateral closing wedge osteotomy (PLCWO), and intermetatarsal suture button fixation procedures on the length and dorsiflexion of the first ray. Methods: We retrospectively evaluated 105 feet in 99 patients with 30 weeks of follow-up. The average age was 54 years. Seventy-four feet had a Lapidus procedure, 12 had a PLCWO, and 19 had intermetatarsal suture button fixation. Digital radiographic measurements were made for the pre- and postoperative hallux valgus angle (HVA) and intermetatarsal angle (IMA), absolute and relative shortening of the first ray, and dorsiflexion. Results: Preoperative HVA and IMA did not differ between treatment groups ( P > .05 for each). Similar corrections of HVA (30.5-13.5 degrees) were achieved between all groups ( P > .05). The IMA was improved more in the Lapidus group (14.3-6.5 degrees) compared with the suture button fixation group (14.2-8.1 degrees) ( P = .045). There were significant differences in the change in absolute first cuneiform–metatarsal length (FCML) between the Lapidus (–1.6 mm), PLCWO (–2.3 mm), and intermetatarsal suture button fixation (+1.9 mm) procedure ( P = .004). There were also significant differences in relative first metatarsal shortening between the Lapidus (0.1 mm relative shortening), PLCWO (1.1 mm relative shortening), and intermetatarsal suture button fixation (1.3 mm lengthening) procedure ( P < .001). The average dorsiflexion differed between the Lapidus (1.8 degrees) and suture button fixation (0.4 degrees) groups ( P = .004). Conclusion: Intermetatarsal suture button fixation relatively lengthened the first ray, the Lapidus procedure maintained length, and the PLCWO relatively and absolutely shortened it. Dorsiflexion may be higher with the Lapidus and osteotomy procedures. Level of Evidence: Level III, retrospective comparative series.